Brief to the 2024-2025 Pre-budget Consultation - Quebec Community Groups Network (QCGN) (2024)

Mémoire présenté dans le cadre de la consultation prébudgétaire 2024-2025 - Quebec Community Groups Network (QCGN) (2024)

Annual Report 2023-2024 - Provincial Employment Roundtable (PERT) (2024)

What Is a Home & School Association? And What Can It Do for Your School Community? - Quebec Federation of Home and School Associations (QFHSA) (2024)

Plan stratégique / Strategic Plan 2022-2026 - NDG Community Council (NDGCC) (2023)

Bilan annuel : CSC - Plan d'action 2023-2024 - Leading English Education and Resource Network (LEARN) (2023)

Strategic Plan 2024-2027 : The Way Forward - Provincial Employment Roundtable (PERT) (2023)
The Provincial Employment Roundtable (PERT) is a non-profit multi-stakeholder initiative focused on addressing the employment and employability challenges facing Québec’s English-speaking community. This strategic plan for 2024-2027 outlines five key shifts, the introduction of a third organisational pillar, and eleven strategic goals that will guide PERT’s efforts to address the unique employment challenges faced by English speakers in Québec.

Seniors Action Quebec Announces Change to Board of Directors - Seniors Action Quebec (SAQ) (2022)

Press Release : Seniors Action Quebec Announces Appointment of New Executive Director - Seniors Action Quebec (SAQ) (2022)

Roles and Responsibilities : CLC Team Members, School Boards and LEARN's Provincial Resource Team - Leading English Education and Resource Network (LEARN) (2022)

41st Annual General Meeting - Voice of English-speaking Quebec (VEQ) (2022)

Minutes of the Annual General Meeting of “Agape” Inc. - AGAPE (2022)

Update on Strategic Plan 2022 -2026 / Point d'information sur le plan stratégique - Garcia, Patricia (2022)

Rapport du Comité de résidents du Jeffery Hale : Année 2021-2022 - Cloutier, Robert (Jeffery Hale - Saint Brigid's (JHSB), 2022)
Au cours de 2021-2022, le Comité de résidents du Jeffery Hale a tenu dix séances de travail via Zoom compte tenu des exigences sanitaires Covid-19. Ce mode de fonctionnement a permis aux membres du Comité de maintenir le lien d’appartenance et de réaliser des projets d’amélioration de la qualité de vie des résidents et leurs proches.

[Jeffery Hale - Saint Brigid’s Users’ Committee Annual Report: 2021-2022] - Jeffery Hale – Saint Brigid’s Users’ Committee (Jeffery Hale - Saint Brigids (JHSB), 2022)
The Jeffery Hale-St. Brigid’s Users’ Committee met ten times from April 2021 to March, 2022 plus at the Annual Meeting on June 7, 2021. There were no in-person meetings held because of the Public Health constraints imposed by the COVID 19 worldwide pandemic so all meetings were held through Zoom. Some of the main challenges this public health situation has presented to the Committee have been the difficulty of meaningfully supporting staff in both residences, limited in- person access to Residents and their families, recruiting new members, and the complications in planning and implementing programmes.

Comité des usagers : Rapport annuel 2021-22 - Comité des usagers Jeffery Hale - Saint-Brigid’s (Jeffery Hale - Saint Brigids (JHSB), 2022)
Le Comité des usagers Jeffery-Hale-Saint-Brigid’s s’est réuni à dix (10) reprises entre le mois d’avril 2021 et mars 2022, avec une réunion générale annuelle le 7 juin 2021, par la plateforme ZOOM. Il n’y a pas eu de séances en présentiel, compte tenu de la pandémie COVID-19. Parmi les principaux défis pour le comité, en raison de cette situation d’urgence sanitaire, il y avait la difficulté à apporter un soutien significatif au personnel dans les deux établissements, l’accès restreint aux résidents et leurs familles, la difficulté de recruter de nouveaux membres pour les comités ainsi que de planifier et mettre en œuvre des programmes.

AGM Minutes : March 22, 2022 - Griffin, Priscilla (Coasters Association, 2022)

Follow-up Report - Maurice, Cornella (Coasters Association, 2022)

A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)
The Plan is meant to articulate the needs, the issues, and the priorities of Québec’s English-speaking youth community (ages 16 – 30) It is a living document that will be reviewed and adapted over the 5-year span to reflect the changing needs within the community and the world.

Annex : A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)

Strategic Restructuring Plan : The Road Ahead - Maurice, Cornella; Buffitt, Kimberly; Fequet, Roderick; Keats, Shannon; Griffin, Priscilla; Maynard, Hugh; Geukjian, Nadia (Coasters Association, 2022)

Améliorer la santé et le bien-être des aînés d’expression anglaise vivants dans les Laurentides au Québec - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
La présente évaluation des besoins a été réalisée à la demande du Réseau communautaire des Laurentides 4Korners, un organisme caritatif canadien enregistré qui a été fondé en 2005 dans le but de faire connaître aux citoyens des Laurentides les programmes et les services qui répondent à leurs besoins dans un environnement sécuritaire et inclusif. Elle a pour objectif de déterminer les besoins de la population âgée d’expression anglaise des Laurentides et de vérifier si ces besoins sont présentement satisfaits. Cette évaluation a été menée par le Conseil scolaire des Premières Nations en éducation des adultes, en collaboration avec la firme de consultants S.O.A.R. Solutions. Les travaux ont été réalisés sous la supervision du Comité d’évaluation des besoins des aînés (SNAC), lequel est composé de membres du personnel de 4Korners, du Elders’ Community Worker du Centre de santé Kanesatake, de bénévoles et de consultants en projets du Conseil scolaire des Premières Nations en éducation des adultes.

Improving the Health and Well-being of English-speaking Seniors in the Laurentians, Québec : A Needs Assessment - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
This needs assessment was commissioned by the 4Korners Laurentian Community Network, a registered Canadian charitable organization founded in 2005, which connects individuals of the Laurentians with programs and services to meet their needs in a secure and inclusive environment. The objective was to identify the needs of the aging English-speaking population in the Laurentians and to determine if they are currently being met. The First Nations Adult Education School Council conducted the assessment in partnership with S.O.A.R. Solutions, a consulting firm. The work was overseen by a committee (the Seniors’ Needs Assessment Committee, SNAC), made up of 4Korners employees, volunteers, the Elders’ Community Worker from the Kanesatake Health Center and project consultants from the First Nations Adult Education School Council.

Senior Safety Plan : Raising Awarness of Elder Abuse on the Lower North Shore - Maurice, Jenna; Kippen, Kayla (Coasters Association, 2022)

Resolution 2022-04 : Request to Be Included in Future Consultations as a Partner in Education - Quebec Federation of Home and School Associations (QFHSA) (2022)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Council for Magdalen Islanders (CAMI), 2022)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

Community Development Plan 2022-2027 : Roundtable - Quebec Community Groups Network (QCGN) (2021)

Press Release : Seniors Action Quebec Announces Change in Executive Leadership - Seniors Action Quebec (SAQ) (2021)

The Regional Association of West Quebecers Announces 2021-2022 Board of Directors - Ayers, Arthur (2021)

Strategic Intervention Plan : English Federal Correctional Services in Quebec - Quebec Community Groups Network (QCGN) (2021)

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Current Situation Report : Data Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.
Keywords: Official Language Minority Community (OLMC)

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Current Situation Report : Funding Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.
Keywords: Official Language Minority Community (OLMC)

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Environmental Scan Report : Organization and Network Health Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Environmental Scan Report : Representation Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.

Executive Director's Report : April 2020 to March 2021 - Coasters Association (2021)
This report of activities of the Coasters Association Inc. have been prepared in order to provide the Board of Directors with general information and summary of the work carried out since April 1st,2020 to March 31st, 2021, as outlined in the activities of the contribution agreement of Canadian Heritage.

AGM Minutes - Coasters Association (2021)

AGM Minutes - Coasters Association (2021)

Follow-up Report - Maurice, Cornella (Coasters Association, 2021)

Crisis Management Planning Guide - Literacy Quebec (LQ) (2021)

Crisis Management Planning - Reference Document - Literacy Quebec (LQ) (2021)

Crisis Management Planning Tool Kit - Literacy Quebec (LQ) (2021)

Embracing Change and News Leadership, QCGN Wraps Up 25th Annual General Meeting - Quebec Community Groups Network (QCGN) (2020)

[Letter to House Leaders from Geoffrey Chambers, QCGN President] - Chambers, Geoffrey (2020)

Tips for an Engaging Online Workshop - Leading English Education and Resource Network (LEARN) (2020)

Composition du Comité des usagers du Jeffery Hale - Saint Brigid's - Jeffery Hale - Saint Brigid's (JHSB) (2020)

[Jeffery Hale Residents' Committee List / Jeffery Hale comité des résidents liste de membres] - Jeffery Hale - Saint Brigid's (JHSB) (2020)

Saint Brigid's Residents' Committee / Saint Brigid's comité des résidents - Jeffery Hale - Saint Brigid's (JHSB) (2020)

2019-2020 Annual Report : Saint Brigid's Home Residents' Committee - Leger, Valerie (Jeffery Hale - Saint Brigids (JHSB), 2020)
The roles and responsibilities of our Residents’ Committee (shared with the Users’ Committee) are to: 1. Inform users of their rights and obligations. 2. Help improve the quality of living conditions and evaluate the degree of satisfaction with the services at the institution. 3. Defend the collective rights and interests of users or, upon request, the rights and interests of an individual user, before the institution or any competent authority. The SBH Residents’ Committee is overseen by the JHSB Users’ Committee. As president, I therefore attended its meetings to receive and give information of interest to SBH. As committees we strive to work closely with administrators at SBH to ensure our concerns translate into quality services for residents.

Rapport du Comité des résidents du Jeffery Hale : Année 2019-2020 - Cloutier, Robert (Jeffery Hale - Saint Brigid's (JHSB), 2020)
Au cours de l’année 2019-2020, le Comité des résidents du Jeff s’est rencontré à sept reprises. Les rencontres se sont tenues principalement au 2e étage du Jeff le troisième vendredi du mois. Étant donné la venue du Coronavirus le Comité a tenu sa dernière séance le 21 février 2020. Par ailleurs, des communications téléphoniques et par courriel ont lieu régulièrement avec les membres. Le Comité est composé de résidents, de proches aidants et d’ex proches aidants. Pour que tous les membres s’impliquent dans les travaux du Comité et que les séances de travail soient plus productiv

[Jeffery Hale - Saint Brigid’s Users’ Committee Annual Report : 2019-2020] - Jeffery Hale – Saint Brigid’s Users’ Committee (Jeffery Hale - Saint Brigids (JHSB), 2020)
The Jeffery Hale – Saint Brigid’s Users’ Committee met nine times from April 2019 to February 2020 in addition to its Annual Meeting on May 8, 2019. The Annual Meeting was held in conjunction with an Information Meeting by the Administration for Saint Brigid’s Residents and families and was well attended. The March 2020 meeting was cancelled because of the Covid19 virus pandemic. Throughout the year the Committee’s meetings were held in the Saint Brigid’s Boardroom because of renovations to the Jeffery Hale Pavilion.

Profil des jeunes anglophones des Laurentides 15 à 29 ans - 4Korners (2020)
Selon les données publiées par l’Institut de la statistique du Québec en 2020, la population vivant dans les régions administratives de la province a considérablement changé de 2019 à 2021 en raison des répercussions sociales directes de la pandémie de COVID-19 et de ses conséquences sur la migration, la mobilité, l’attractivité de la main-d’oeuvre, la conciliation travail-famille, les habitudes de vie et les loisirs. Ainsi, on estime que 632 000 habitants vivaient dans la région des Laurentides au 1er juillet 2020, marquant une augmentation de 17,7 % pour l’année 2019-2020; ce pourcentage est plus élevé que le taux moyen de l’ensemble de la province (8,5 %) pour cette année. De fait, il est important de souligner que cette région présente la plus forte augmentation depuis le début de la pandémie en mars 2020.

Profile of Laurentian English-speaking Youth 15-29 - 4Korners (2020)
According to data published by the Institut de la statistique du Québec in 2020, the population living in the administrative regions of the province has significantly changed between 2019 and 2021, being directly affected by the social impacts caused by the COVID-19 pandemic and its implications for out-migration, mobility, workforce attractivity, work/life balance, lifestyle habits and leisure activities. As a result, it is estimated that 632,000 inhabitants were living in the Laurentian region as of July 1, 2020. This represents an increase of 17.7% for the year 2019-2020, which is higher than the average rate across the province (8.5%) for that year. In fact, it is important to highlight that this region presents the largest increase since the outbreak of the pandemic in March 2020.

AGM Minutes : Annual General Report - Coasters Association (2020)

Lower North Shore Housing Needs Assessment - Kippen, Kayla (2019)
Communities in rural remote regions often struggle with access to services across the province and other parts of Canada. These access issues are often worsened during times of crisis. A significant problem facing rural communities is the current housing structure for vulnerable people. For example, those requiring palliative care services, or facing mental health and dependency issues, are particularly confronted with issues when trying to secure or obtain stable housing, or access to supportive housing programs and services. In 2017, the federal government announced its first ever National Housing Strategy for Canadians, with a goal of making sure Canadians across the country can access housing that meets their needs and that they can afford. With the witnessed economic downturns, poverty and unemployment rates of the region, it was necessary to investigate whether the Lower North Shore was also providing access to housing that meets the needs of all citizens.

Assessment of the Priority Setting Process for the English-speaking Communities of Quebec (ESCQ) : Guide for the Focus Groups - Canada. Department of Canadian Heritage; Quebec Community Groups Network (QCGN); KSAR & Associates (2019)

CAMI’s Annual General Meeting : 2018-2019 - Council for Anglophone Magdalen Islanders (CAMI) (2019)

Annual Report / Rapport Annuel 2018-2019 - Quebec Community Groups Network (QCGN) (Quebec Community Groups Network (QCGN), 2019)
Keywords: Official Language Minority Community (OLMC)

Strategic Priorities Forum : 2018 – 2019 Priorities of the English-speaking Community of Quebec and Annual Report of the Priority Setting Steering Committee - Quebec Community Groups Network (QCGN) (2019)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary; Maynard, Hugh; Burke, Helena; Brinklow, Laurie; Mulligan, Marleen (Council for Magdalen Islanders (CAMI), 2019)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

Report of the Planning Committee on the 2018 Members’ Forum - McGill Community For Lifelong Learning (MCLL) (2018)
A Members’ Forum was held on 26 October 2018 to discuss the issue of peer learning at MCLL. The three major findings and the four recommendations are presented here

NDG Community Strategic Action Plan 2016-2021 : List of Annexe : Part II - NDG Community Council (NDGCC) (2018)
This document is the first of three that collectively represent the NDG Community Strate- gic Plan 2016-2021. Part I is a report on the strategic planning and action planning pro- cess and presents the context, tools and outcomes of the NDG Community Strategic Plan. Part II includes annexes to this report with details, tools and other data. Part III presents the Action Plan 2018-2021.

NDG Community Strategic Action Plan 2016-2021 : Part I - NDG Community Council (NDGCC) (2018)
This document is the first of three that collectively represent the NDG Community Strate- gic Plan 2016-2021. Part I is a report on the strategic planning and action planning pro- cess and presents the context, tools and outcomes of the NDG Community Strategic Plan. Part II includes annexes to this report with details, tools and other data. Part III presents the Action Plan 2018-2021.

Regional Tourism Action Plan for the English-speaking Community of the Gaspé and Magdalen Islands 2018-2023 - Harrison, Kim (Committee for Anglophone Social Action (CASA), 2018)
The Committee for Anglophone Social Action (CASA) works to build and strengthen the vitality of the English-speaking community of the Gaspé Coast This regional tourism action plan has been developed to foster the increased participation in the tourism industry by English speakers and encourage a greater number of English speakers to visit the Gaspé Coast and the Magdalen Islands. The English-speaking community of the region faces many socio-economic challenges as compared to the francophone population. Increased participation in tourism industry would generate social and economic benefits at the individual, organizational and community level. A recent study commissioned by the Community Economic Development and Employability Committee has indicated a high level of interest by American and Ontarian travellers in visiting the attractions of the English-speaking Quebec, as well as the desire to receive English services when visiting the province.
Keywords: Official Language Minority Community (OLMC)

Strategic Plan 2018-2023 - Coasters Association (2018)
The Lower North Shore of Québec stretches from Blanc Sablon (at the Labrador border) to Kegaska (opposite the eastern tip of Anticosti Island). Sixteen (16) communities, including the two (2) native communities of Pakua Shipi and Uanamen Shipu, are spread along 400 kilometres of rugged coastline, and in most cases are accessible only by boat, plane or snowmobile (in winter). Due to the vastness and isolation of the region, transportation costs are extremely high and often unreliable due to extreme weather conditions. This remote region, which is majority English-speaking, has witnessed a significant decline in population over the last few decades due to the collapse of the region’s main economic activity (the cod & salmon fishery), and the decline in the snow crab fishery. It is estimated that approximately half of the region’s adult population leaves the Coast at some time during the year to secure employment elsewhere. Many leave the territory for several months at a time while their family remains on the Lower North Shore which results in social dislocation as, in some cases, both parents leave for work and their children are housed with grandparents or other family members. Many social challenges have emerged from the changing circumstances, such as caring for the elderly, and many youth leave and do not return due to the lack of job opportunities.

CLC Extended Model : Learnings & Next Steps from the First 4 Years - Estuaries Learning Consulting Group (Leading English Education and Resource Network (LEARN), 2018)
From January to March of 2018, LEARN undertook an evaluation of the CLC extended model that looked to answer two key questions: 1) Has the CLC extended model been a success, and; 2) What best practices can schools and school boards adopt to effectively introduce the CLC extended model? In asking these questions, LEARN was looking to support two specific types of stakeholders: 1) Schools and school boards wanting to understand the benefits and outcomes of the extended model; and, 2) Schools and school boards wanting a deeper understanding of how to extend effectively. The majority of school boards currently have CLCs that have been extended models for a short duration. The data presented here reflects this, as it responds to question two more fully. It will be useful to do a further evaluation in a few years’ time to gather more precise data on the success of the model, once schools have engaged with it for a longer period.

Project Report : Presented by Lower North Shore Housing Corporation - Kippen, Kayla (2018)
The Corporation d’habitation de la Basse-Cote-Nord, or Lower North Shore Housing Corporation (LNSHC), was legally registered as a non-profit organization in October 2018. The Housing Corporation was an initiative presented by the Coasters Association, and other organizations, to develop an affiliate corporation that would manage housing programs and services for the region. Over the past year of the project, there have been many achievements and challenges. There has been a great amount of effort put in by all those associated with this project. It is clear that the Housing Corporation is an important initiative to the representatives and citizens of the Lower North Shore. It is for this reason that we must continue to work towards exploring funding avenues to support the continuance of this project.

Regional Priorities : QCGN Members 2018 - Quebec Community Groups Network (QCGN) (2018)
This document is a collaborative effort on the part of the regional member organization's of Quebec Community Groups Network to ensure regional priorities are at the fore of the Priority Setting Steering Committee discussions and to establish preferred and inclusive methods of consultation among regional member groups.

Action Plan : Westhaven Neighborhood Committee - Westhaven Neighborhood Committee (2017)

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands 2017-2020 - Community Health and Social Services Network (CHSSN); Council for Anglophone Magdalen Islanders (CAMI); Vision Gaspé-Percé Now; Committee for Anglophone Social Action (CASA) (2017)
The official language minority community of this region has the poorest socioeconomic status in Canada when aspects such as low education levels, unemployment and low income tendencies are analyzed. Children are particularly affected by this status. Children ages 0 to 5 make up 6.6% of the total English-speaking population.
Keywords: Official Language Minority Community (OLMC)

The Community Learning Centre Initiative : Framework for Action - Smith, William J. (Leading English Education and Resource Network (LEARN), 2016)
In the province of Quebec, English language-minority communities do not always have equitable access to education, health and/or social services. This challenge is particularly acute for English educational institutions and communities, especially in those regions where Anglophones make up a small percentage of the total population and the English school is the only English- language public sector institution in the community. The Community Learning Centre (CLC) Initiative helps to address this gap by building partnerships between English schools and organizations/institutions in their communities. These partnerships, facilitated by a Community Development Agent (CDA), leverage resources that benefit students, their families and the broader community. Recognizing the value of the CLC Initiative, the Association of Directors General of English School Boards of Québec (ADGESBQ) has supported its development since its inception.

Towards Renewing the Strategic Priorities of the English-speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2016)

Cultural Tourism and Touring Research - Nasrallah, Dimitri (2016)

A New Multi-year Official Languages Plan to Support Canada’s English Linguistic Minority Communities - Quebec Community Groups Network (QCGN) (2016)
This aim of this document is to outline the strategic priorities of the English-speaking Community of Quebec (ESCQ), and its high-level expectations from a new multi-year Official Languages Plan to support Canada’s English linguistic minority communities. Sector and regional leaders have developed their own priorities and expectations, which the strategic priorities contained hereunder support.
Keywords: Official Language Minority Community (OLMC)

Sustaining Impact in CLC Schools and Communities : Provincial Resource Team Report : 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

2017-2018 Priorities of the English-speaking Community of Quebec and Annual Report of the Priority Setting Steering Committee - Strategic Priorities Forum (Quebec Community Groups Network (QCGN), 2016)
In September 2011, the Quebec Community Groups Networks launched The Strategic Priorities Forum, a standing five-year cyclical process to identify common priorities ensuring a vital and sustainable future for Quebec’s English-speaking communities and to collectively pursue enabling strategies to achieve community goals over five years. In this capacity, the QCGN established a nine-member Priority Setting Steering Committee (PSSC), a permanent Committee of QCGN’s Board of Directors, to assist the community with the governance of the Strategic Priorities Forum.

Community Consultation 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

La communauté d'expression anglaise de la [de la] grande région de Québec - Voice of English-speaking Quebec (VEQ) (2016)

Partner Survey 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

The English-speaking Community of the Greater Quebec Region - Voice of English-speaking Quebec (VEQ) (2016)

NDG Community Action Plan 2015 - NDG Community Council (NDGCC) (2015)

[Complaint or Positive Comment Form / Formulaire de plainte ou commentaire positif] - Jeffery Hale - Saint Brigid's (JHSB) (2015)

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

NDG Community Action Plan 2014 - NDG Community Council (NDGCC) (2014)

NDG Community Strategic Plan 2013-2016 - NDG Community Council (NDGCC) (2014)

Règlement : Procédure d'examen des plaintes - Jeffery Hale - Saint Brigid's (JHSB) (2013)
Ce règlement sur la procédure d’examen des plaintes des usagers de l’Hôpital Jeffery Hale - Saint Brigid’s a été élaboré à partir d’un projet-type de règlement élaboré par l’Association québécoise d’établissements de santé et de services sociaux du Québec, notamment par Me Sonia Amziane, avocate-conseil à l’AQESSS, avec la collaboration de Me Sylvain Poirier du cabinet de Heenan Blaikie, dans le contexte de l’entrée en vigueur de la Loi modifiant la Loi sur les services de santé et les services sociaux et d’autres dispositions législatives (L.Q. 2005, c. 32) (projet de loi no 83).

Strategic Plan 2012 - 2015 : Summary Document - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Priorités d'action 2013-2014 : Document global - Jeffery Hale - Saint Brigid's (JHSB) (2013)
Issu de la communauté d’expression anglaise de la grande région de Québec et investi de sa longue tradition d’entraide, l’Hôpital Jeffery Hale – Saint Brigid’s est un établissement public bilingue sous gouvernance participative, engagé à offrir des services sécuritaires de la plus haute qualité empreints de compassion. Il contribue concrètement à la santé et au bien-être de la population de la région en collaboration avec ses partenaires du réseau de la santé et des services sociaux et de la communauté à travers ses services communautaires et généraux de première ligne pour tous les groupes d’âges de même que ses services variés destinés aux personnes en perte d’autonomie. L’Hôpital Jeffery Hale – Saint Brigid’s joue un rôle central de soutien à la communauté d’expression anglaise et à sa vitalité. Il assume le leadership d’actions concertées visant à contribuer au développement de cette communauté et à la santé et au bien-être de ses membres.

2013-2018 Strategic Plan - Quebec Community Groups Network (QCGN) (2013)
English-speaking Quebec is a diverse, confident, recognized and respected national linguistic minority that actively participates in and contributes to the social, economic, cultural and political life of Quebec and Canadian society.
Keywords: Official Language Minority Community (OLMC)

Plan de sécurite des usagers - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Planification stratégique : 2012-2015 - Jeffery Hale - Saint Brigid's (JHSB) (2012)
Le présent document est le résultat d’une démarche entreprise par le conseil d’administration de l’Hôpital Jeffery Hale – Saint Brigid’s, il y a plus d’un an. À la suite de multiples consultations auprès de nos instances internes et externes, le conseil a élaboré les orientations stratégiques sur lesquelles nous fonderons nos actions pour les prochaines années. Elles sont présentées à nos partenaires externes suite à son adoption au printemps 2012.

Communications Assembly June 9, 2012 : Brief from the English Speaking Catholic Council - McDaid, Mary (English Speaking Catholic Council, 2012)
The English Speaking Catholic Council appreciates the opportunity to participate in this General Assembly convened by Bishop Thomas Dowd on the future of communications within the English Sector of the Archdiocese of Montreal.

Strategic Plan 2012-2017 - Coasters Association (2012)
The Lower North Shore of Québec stretches from Blanc Sablon (at the Labrador border) to Kegaska (opposite the eastern tip of Anticosti Island). Sixteen (16) communities, including the two (2) native communities of Pakua Shipi and Uanamen Shipu, are spread along 400 kilometres of rugged coastline, and in most cases are accessible only by boat, plane or snowmobile (in winter). Due to the vastness and isolation of the region, transportation costs are extremely high and often unreliable due to extreme weather conditions. This remote region, which is majority English-speaking, has witnessed a significant decline in population over the last few decades due to the collapse of the region’s main economic activity (the cod & salmon fishery), and the decline in the snow crab fishery. It is estimated that approximately half of the region’s adult population leaves the Coast at some time during the year to secure employment elsewhere. Many leave the territory for several months at a time while their family remains on the Lower North Shore which results in social dislocation as, in some cases, both parents leave for work and their children are housed with grandparents or other family members. Many social challenges have emerged from the changing circumstances, such as caring for the elderly, and many youth leave and do not return due to the lack of job opportunities.

Public Health Action Plan for the English-Speaking Community in the Capitale-Nationale Region 2011-2015 - Jeffery Hale - Saint Brigid's (JHSB) (2011)
Saint Brigid’s – Jeffery Hale Hospital’s Public Health Action Plan for the English- Speaking Community in the Capitale-Nationale Region is in keeping with the Plan d’action regional (PAR) en santé publique 2009-2012 (regional public health action plan) developed by the Agence de la santé et des services sociaux de la Capitale-Nationale (Agence). To ensure viable results for our efforts aimed at improving the health and well-being of the English-speaking community, we thought it relevant to begin by presenting an updated portrait of the English-speaking community in the CNR. This portrait allows us to identify the various needs of the community, as well as its health determinants and indicators, and take stock of its ongoing evolution. This description is followed by a detailed presentation of Saint Brigid’s – Jeffery Hale Hospital’s prevention and health promotion Service Offer.

Membership Socio-demographic Attributes 2010-11 - Voice of English-speaking Quebec (VEQ) (2011)

Strategic Plan : 2011-2016 - The English Speaking Catholic Council (ESCC) (2010)

Coasters Association Inc. Presentation to the Standing Senate Committee on Official Languages - Coasters Association (2010)
The Lower North Shore, with a total population of less than six thousand, consists of fourteen (14) isolated communities, twelve predominantly English speaking, two Francophone communities, and two Montagnais reserves (Five municipalities.) These communities are spread over 550 km on the North East coast of Quebec.
Keywords: Official Language Minority Community (OLMC)

Creating Spaces for Young Quebecers : Strategic Orientations for English-speaking Youth in Quebec - Quebec Community Groups Network (QCGN) (2009)
Over the past decades, Francophones in Quebec have taken formal steps to preserve and promote their language and culture. To most English-speaking youth growing up in Quebec today, this makes sense and we agree that steps should be taken to protect Quebec’s uniqueness in North America. However, young English-speakers living in Quebec - from Montreal to the North Shore to the Gaspé - face their own set of unique challenges. In small English-speaking pockets scattered throughout the province, young English-speakers struggle to become bilingual, access services, create strong ties with their communities, participate in Quebec society and define their own identities. The members of the Quebec Community Groups Network (QCGN) Youth Standing Committee have worked together over the last year to ensure that this document represents the perspectives of as many youth as possible from a wide array of regions and backgrounds. We have also worked to ensure that the process has been directed by youth and that the voices we have heard are heard by others as well. This is the first time that a significant percentage of English-speaking youth in Quebec have come together from across many regions to address the barriers young people face. It has been exciting to discuss our Quebec roots, our desire to remain in this province and our willingness to move past the linguistic tensions of previous generations. In consultations across eight regions, followed by a provincial forum, we have generated strategies for moving forward together. This document outlines strategies that youth have recommended to help achieve our collective vision for English-speaking youth in Quebec. We encourage the QCGN to work towards this vision for English-speaking youth in Quebec in collaboration with community partners, all levels of government and Francophone organizations.
Keywords: Official Language Minority Community (OLMC)

French Immersion Teen Camp : Feasibility Study - Newcombe, Vanessa; Roberts, Carla; Griffin, Emily (Coasters Association, 2008)
Living in such an isolated area such as, the Lower North Shore, there is a lack of activities for all ages, but more so for the adolescent age. There are very few activities on the Lower North Shore that directly focuses on teenagers, so teens resort to other activities that result in social problems (i.e. drinking, drugs, vandalism, etc…). Therefore, a French Immersion Teen Camp would provide teenagers with activities and a program that is especially designed for them. Teenagers could have a chance to get away from the social problems and into a program that will nurture and develop a safe and healthy environment in which the teens can improve their health and obtain skills that will assist them in their future lives and also promote and develop their French as a Second Language skill.

2008 Youth Consultation on the Lower North Shore - Buckle, Heidi (Coasters Association, 2008)
The 2008 Lower North Shore Youth Consultation was coordinated to provide a needs assessment of the English-speaking youth on the coast, addressing topics related to youth retention and youth out migration. The projected outcome of the consultation was to empower youth with a collective identity and to encourage greater participation within the Lower North Shore at large.

Strategic Plan : 2005-2006 to 2008-2009 - The English Speaking Catholic Council (ESCC) (2005)

Report from the Executive Director - Hook, Deborah (Quebec Community Groups Network (QCGN), 2004)

QCGN President's Report 2003-2004 - Murphy, Martin P. (Quebec Community Groups Network (QCGN), 2004)
The Quebec Community Groups Network (QCGN) has been in existence on a formal basis since 1995. Much has been accomplished in these past nine years. Looking to the future, there are many challenges which require our attention, strong leadership and innovative ideas to enrich our identity and resolve. It is imperative that the QCGN conrinue to buiid its credibility as a strong and unhesitating voice of reason in working to enhance the development of the English-speaking minority population in Quebec.

President's Report on Highlights of Activities Representing QCGN : June 2002 - June 2003 - Murphy, Martin P. (Quebec Community Groups Network (QCGN), 2003)

Quebec Community Groups Network : Executive Director's Report 2002-2003 - Hook, Deborah (Quebec Community Groups Network (QCGN), 2003)
The year 2002-2003 has once again been an exciting year of growth and deveiopment for the QCGN. Through the many activities undertaken over the past year, we have re-enforced the solidarity among our members and extended our outreach past the QCGN membership into the broader English-speaking community of Quebec.

Global Development Plan : Strategy to Revitalise the English Language Minority Communities of Quebec : Arts & Culture Plan - Quebec Community Groups Network (QCGN) (2003)
The Global Development Plan initiative originates from a request of the Federal Government to develop a funding framework. The GDP represents an opportunity for the English-speaking community to take charge of its current stage and identity within Quebec. This would include developing a clearer picture of the English-speaking population of Quebec, where it comes from and where it's going; helping maintain the population base by encouraging a sense of belonging; raising the profile and participation level of English-speaking people at the municipal, institutional and govemment levels; promoting employment opportunities within the community for English speaking youth; initiating community projects; and maintaining dialogue with governments in the francophone community.

Suggesting Change : The Situation of the English-speaking Minority of Quebec and Proposals for Change - Quebec Community Groups Network (QCGN) (2002)
Actions by the Government of Canada, such as the Speech from the Throne in January 2001, the nomination of Minister Stéphane Dion to coordinate the Federal Government's policy on official languages and chair the team of Ministers directly involved in Official Languages Policy and Program and his desire to develop an action plan to support the application of the Official Languages Act are encouraging. The demonstration of the political will of the Government to fulfill its obligation to ensure the full support of the development of vibrant and healthy Official-language minority communities throughout Canada is absolutely essential. It is, thus, incumbent on the Government that there is understanding and acceptance of the needs and realities of each linguistic minority community by both the majority populations and by those within the Canadian Government whose job is to develop and implement policy in support of the Francophone and Anglophone minority communities. The Official Languages Act must ensure the means and mechanisms for coordinated action and mobilization of the necessary resources to empower official minority language communities. As such, the action plan put forward by Minister Dion must be aimed at enabling the English-speaking minority in Quebec to build its own capacity, using solid facts and broad-based knowledge to be able to work with all governments to maintain and develop strong, vibrant English-speaking communities throughout Quebec.

Global Development Planning for the English-language Minority Communities of Quebec : Working Group Report Phase 1 : Preparation and Review - Quebec Community Groups Network (QCGN) (2002)
The Global Development Plan (GDP) Working Group has prepared the following report, which presents the conclusions and recommendations of the first phase of the GDP project entitled, Preparation and Review. This report is intended to guide the reader through the Working Group's reflection, discussion and analysis between December 2001 and March 2002.

Global Development Planning for the English-language Minority Communities of Quebec - Quebec Community Groups Network (QCGN) (2002)
The following discussion paper is a resource document created for the Global Development Plan (GDP) Working Group, which is based on highlights of various readings. The intention of this document is to generate discussion concerning the Quebec English-speaking community in terms of: How has the community evolved? Where are we now? Who are we?

Africana Congress 2000 - Africana Studies Committee (2000)
Africana Congress 2000 was held at McGill University from February 4" to February 6” 2000. Organized by the Africana Studies Committee and the Black Student Network, and sponsored in large part by Canadian Heritage, the event served to celebrate and critically re-evaluate 30 years of Africana Studies at McGill University. The Congress marked a major turning point in the struggle to maintain and promote Africana Studies at McGill University. It was first conceived two years earlier, when the Africana Studies Committee (ASC) drafted its 1998 Development Plan, a document that charted ASC’s 20-year vision for the potential expansion of the program. The plan was divided into four phases, the final one being the establishment of an Africana Studies Centre. In the interim, the Congress was conceived and proposed as a way of mobilizing as much support for the initiative as possible. The Congress was also conceived as a forum that would welcome input and would generate discussion about how to achieve our goals. ASC without engaging in acknowledged that it could not achieve these ambitious, though not unrealistic, goals with genuine consultations with the wider community.

Alliance Quebec Identifies Priorities for the Coming Year - Alliance Quebec (AQ) (1999)

Alliance Quebec is No Shell - Alliance Quebec (AQ) (1999)

Alliance Quebec - Coming Initiatives - Alliance Quebec (AQ) (1998)

Le comité régional (Montreal) du Congrès national des femmes noires : Rapport - Le Comite Regional (Montreal) du Congres National des Femmes Noires (1981)
Les buts de cette conference etaient de sensibiliser le public en general (Noir et Blanc) c'est-a-dire, les parents et les enfants, les etudiants et les enseignants, les organisations gouvernementales et para-publiques au racisme et au sexisme, qui existent dans les manuels scolaires de trouver des solutions aces problemes et d'utiliser notre force collective afin d'effectuer les changements sociaux constructifs.

National Regional Committee National Congress of Black Women Report - Montreal Regional Committee National Congress of Black Women (1981)
The objectives of this Conference were aimed at sensitizing the general public (Black and White) i.e. parents and children, students and teachers, governmental and para-public organizations, to the racism and sexism found in the textbooks used in our school system, to develop solutions to these problems and to use our collective strength to bring about constructive social change.

Community Against Drugs (CAD) : A Pilot project for the Municipality of Bonne Esperance - Coasters Association

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of The Magdalen Islands - Council for Anglophone Magdalen Islanders (CAMI)

Youth Engagement Guide & Toolkit - Kippen, Kayla; Etheridge, Honlee (Coasters Association)

[CLC Plan Template] - Leading English Education and Resource Network (LEARN)

Guide to Planning and Hosting Your Community Learning Conversation - Leading English Education and Resource Network (LEARN)

The Partnership Agreement - Leading English Education and Resource Network (LEARN)

Your CLC's Operations Manual Template - Leading English Education and Resource Network (LEARN)

[Quebec Association for Adult Learning Inc. By-Laws] - Quebec Association for Adult Learning (QAAL)

[Quebec Association for Adult Learning Inc. Constitution] - Quebec Association for Adult Learning (QAAL)

Proposed Logic Model for Community Development Plan - Quebec Community Groups Network (QCGN)

Quebec's English-speaking Community Development Plan - Quebec Community Groups Network (QCGN)